DAKWAH TOLERANSI GITA SAFITRI FEAT HABIB HUSEIN JA'FAR DI DUNIA VIRTUAL : ANALISIS CHANEL YOUTUBE GITA SAFITRI DEVI DAN JEDA NULIS - Muhamad Hizbullah; Vonny Aprianty (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2022)
ABSTRACTThe development of communication technology (Internet, social media) makes the global community (global village) unlimited, anyone can be the sender and recipient of messages at the same time, including in terms of preaching. One of the characteristics of digital society is that it is diverse, free, and tends not to be tied down. Therefore, the preaching of tolerance in digital spaces such as YouTube is something that is very important and necessary. Da'wah of tolerance is understood as an effort to invite or call someone to the path of God with approaches that do not offend the interlocutor, do not discriminate against different groups, respect, and prioritize tenderness and compassion. One of the figures who are quite intense in voicing the values of tolerance through YouTube are Gita Savitri and Habib Husen Ja'far through the YouTube channels Gita Savitri and Jeda Nulis. The results of this study indicate that the preaching of tolerance is formed through open-minded, moderate, understanding that da'I is only a messenger, expanding knowledge and opening up space for dialogue with religions outside of Islam. The concept of fastabiqul khairat in the inter-religious public space is to issue the output of the goodness of each religion and synergize in goodness and build humanity. Keywords: internet, preaching tolerance, global village, youtube channel, open minded.